A new user friendly visual environment for breast MRI data analysis. (September 2016) - Danelakis, A.; Toulas, P.; Theoharis, T.; Verganelakis, D.A.
Abstract : Introduction: In recent years, there has been a great effort for the exploitation of powerful computer systems in order to support clinical decisions, the so-called CDSS (Clinical Desicion Support Systems). After processing imaging data in an automatic way they can provide useful diagnostic information facilitating like this clinical decisions. Purpose: This study demonstrates the advantages of a newly developed friendly visual CDSS environment for Breast MRI Data Analysis, the co-called BreDAn. This software process all dynamic MRI data prior and post contrast medium injection generating kinematic graphs, color maps of signal increase and decrease and finally detecting high risk breast areas. The great advantage of BreDAn is the automation of the radiodiagnostic process in a reliable manner. Materials and methods: BreDAn involves a series of steps of MRI Breast data processing, such as data initialization, windowing, intensity filter, intensity curve slope filter, color fragment filter and data display. It has been tested and evaluated using 534 MRI data sets (522 F, age group 31–79 y and 12 M, 55–68 y). A GE Signa HDxt 1.5 Tesla system was used throughout all MRI scans. A description of the MRI protocol is given. Results: Out of the 534 cases studied, 9.55% of them found to be pathological and 90.45% were non-malignant. All automatically generated results by BreDAn were compared by radiologist's diagnosis and found to be in agreement. BreDAn in practice simulates the radiological diagnostic methodology. Conclusion: This study illustrates the advantages of BreDAn, a user friendly visual environment for MRI Breast data analysis, which have been tested thoroughly and validated successfully.